If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3f + -10) = 30 Reorder the terms: 6(-10 + 3f) = 30 (-10 * 6 + 3f * 6) = 30 (-60 + 18f) = 30 Solving -60 + 18f = 30 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '60' to each side of the equation. -60 + 60 + 18f = 30 + 60 Combine like terms: -60 + 60 = 0 0 + 18f = 30 + 60 18f = 30 + 60 Combine like terms: 30 + 60 = 90 18f = 90 Divide each side by '18'. f = 5 Simplifying f = 5
| 80+y^2=0 | | (a-4)*(a+4)= | | 6x+12=-58-8x | | 2x-6=-x+15 | | 3x+9x+10=13 | | 5u(2u+3)-2u(u-7)= | | 2x+127=12x-13 | | 3c^2-3c=4c | | 9-7x=84-42x | | 2x-5x=10 | | 5x^2-55x+20=0 | | 10-7x=103-28x | | x^2-16=-13 | | 112-7x=38+17 | | 140-3x=33x+20 | | 25x^2+11=15 | | 3x^2+18x-25=0 | | x^2-7x=7 | | 74+4x=9x+22 | | -119-7x=84-42x | | (x-5)*(x+8)= | | x^2+12x-5=0 | | x^2+(4-3)=26 | | x^2+4-3=5 | | x+5=105 | | -2=-4+3x | | w=f(a+r) | | 4x^2-7x+11=5x+6 | | 27-8(2-Y)=-13 | | 137-7x=29x+17 | | 27-8(2-7)=-13 | | 10x-2=38 |